Implementation of Automatic Lamp Using Arduino with PIR Sensor - Faizin, Moch Nur; Zulfikar, Zulfikar (NEWTON: Networking and Information Technology, 2025)
This research aims to design and implement an automatic lamp control system using Arduino and Passive Infrared (PIR) sensors to reduce electrical energy waste due to human negligence. The system uses two PIR sensors placed in sequence at the entrance to detect human movement and determine the direction of entry or exit. Arduino Uno is used as the microcontroller to process sensor inputs and control the relay that switches the AC lamp on or off. The testing results show that the system works effectively in distinguishing between entry and exit movements. The PIR sensors perform optimally at a distance of 1–2 meters with a response time of less than 500 ms and reliability reaching 100%. The system successfully saves energy by ensuring that the lamp only lights up when someone is inside the room and turns off automatically when the room is empty.